Effects of coagulation and calcium ions on dead end and cross-flow nanofiltrations of Natural Organic Matter (NOM) - Karina, Listiarini (2011)
Nanofiltration (NF) technology has been widely used in drinking water treatment process and advanced wastewater reclamation due to its capability in effectively removing contaminants down to multivalent ions, while operating at lower pressure compared to reverse osmosis (RO). One of the major challenges in membrane filtration is fouling, since fouling deteriorates the performance of nanofiltration over time. Although many types of foulant can cause fouling, natural organic matter(NOM) is considered as a major foulant due to its recalcitrant properties and the fact that it is commonly found in natural water. In addition to this, the presence of divalent cations such as calcium could add the severity of fouling, as it is capable of forming bonds between NOM and between NOM-membrane surface.